Confirmation on Status of Omotemnus miniatocrinitus Chevrolat (Coleoptera: Dryophthoridae) in Snakefruit Growing Areas - Rangga Arinta Wisastra; Edhi Martono; Suputa Suputa (Universitas Gadjah Mada, 2017)
-